Birth weight discordant twins have increased prenatal mortality and neonatal morbidity: an analysis of 1,132 twins - Sara Domingues; Luísa Neiva Araújo; Ana Guedes; Luísa Lopes (Hygeia Press di Corridori Marinella, 2015)
Background: Multiple pregnancies have increased significantly over the past decades. Birth weight discordance (BWD) is a common problem between twins, but its association with an increased morbidity and mortality is still unclear. The aim of this study was to determine the frequency of BWD among twins and to evaluate its impact on perinatal morbidity. Methods: Retrospective study of 1,132 twins born in a tertiary perinatal center, over a period of 8 years (2003-2010), that were divided in two groups: concordant (intrapair birth weight difference ≤ 20%) or discordant (> 20%). The two groups were compared in terms of epidemiological and obstetric data, mode of delivery, perinatal morbidity and mortality. Results: During the study period, multiple gestation occurred in 2% of cases, of which 96% were twins. BWD was found in 212 (19%) twins. Multivariate analysis demonstrated that maternal age ≥ 35 years and hypoxic-ischemic placental infarction were risk factors for the occurrence of BWD. The discordant group showed a significantly higher incidence of congenital skeletal and central nervous system malformations, a higher rate of hospitalization in the neonatal intensive care unit and a longer duration of hospitalization. The percentage of those requiring assisted ventilation, pulmonary surfactant, parenteral nutrition and central venous catheters was significantly higher in the discordant group compared with the concordant one. The rate of stillbirth was significantly higher in the discordant group (3% versus 1%); mortality was also higher (3% versus 2%), but this difference was not statistically significant (p = 0.405). Conclusion: BWD was associated with increased prenatal mortality and neonatal morbidity. Diagnosis and management of pregnant women with this fetal condition in tertiary perinatal centers may improve the prognosis of these infants.